2016
DOI: 10.1371/journal.pone.0168215
|View full text |Cite
|
Sign up to set email alerts
|

Octreotide LAR and Prednisone as Neoadjuvant Treatment in Patients with Primary or Locally Recurrent Unresectable Thymic Tumors: A Phase II Study

Abstract: Therapeutic options to cure advanced, recurrent, and unresectable thymomas are limited. The most important factor for long-term survival of thymoma patients is complete resection (R0) of the tumor. We therefore evaluated the response to and the induction of resectability of primarily or locally recurrent unresectable thymomas and thymic carcinomas by octreotide Long-Acting Release (LAR) plus prednisone therapy in patients with positive octreotide scans. In this open label, single-arm phase II study, 17 patient… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
12
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(12 citation statements)
references
References 45 publications
0
12
0
Order By: Relevance
“…It has been reported that somatostatin has antiproliferative activity associated with growth factors inhibition, such as insulin-like growth factor-1 and epidermal growth factor, activation of immunity and tumor vessel angiogenesis inhibition. Recently, octreotide Long-Acting Release (LAR) (intramuscular injections of 30 mg/every two weeks) plus prednisolone (0.6 mg/kg/day), for a maximum of 24 weeks, has been evaluated as neoadjuvant treatment in patients with positive octreotide scans in a phase II study [7]. Among 17 patients with primarily unresectable or advanced locally recurrent thymoma (15 cases) or TC, the ORR after 3 months of treatment was 88%, and overall operability after 6 months of treatment was 52%.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…It has been reported that somatostatin has antiproliferative activity associated with growth factors inhibition, such as insulin-like growth factor-1 and epidermal growth factor, activation of immunity and tumor vessel angiogenesis inhibition. Recently, octreotide Long-Acting Release (LAR) (intramuscular injections of 30 mg/every two weeks) plus prednisolone (0.6 mg/kg/day), for a maximum of 24 weeks, has been evaluated as neoadjuvant treatment in patients with positive octreotide scans in a phase II study [7]. Among 17 patients with primarily unresectable or advanced locally recurrent thymoma (15 cases) or TC, the ORR after 3 months of treatment was 88%, and overall operability after 6 months of treatment was 52%.…”
Section: Discussionmentioning
confidence: 99%
“…The reported adverse events associated with octreotide are most common hematological and gastrointestinal, and grade 1 or 2. However, fatal pneumonia, probably caused by thymomaassociated immunodeficiency during steroid medication not to octreotide LAR was reported [7].…”
Section: Discussionmentioning
confidence: 99%
“…Patients with TC display higher serum concentrations of VEGF and b-FGF than patients with TM [ 29 ]. TETs can also express somatostatin receptors (SSTR), providing a rationale for somatostatin’s anti-proliferative effect as a therapeutic option [ 30 , 31 ]. Additionally, mesothelin is expressed with high frequency in TCs and it is potentially targetable [ 32 ].…”
Section: Overview Of Tets Biologymentioning
confidence: 99%
“…SSTRs are expressed in TETs, thus the efficacy of octreotide, a somatostatin analog, with and without prednisone has been investigated by three phase 2 studies [ 30 , 31 , 59 ]. The primary endpoint was the ORR in each study, and was 37%, 31.6%, and 88%, respectively.…”
Section: Characterization Of Tm Biologymentioning
confidence: 99%
See 1 more Smart Citation